(untitled) (Progressive Agriculture, 2020)
The use of agricultural waste is of great interest to sustainable agriculture. An investigation was carried out to evaluate the effects of compost and compost tea made from agricultural waste rice straw on the yield and quality of two horticultural crops strawberry and tomato. In strawberry experiment, six treatments were considered which wereT1: 100% soil (as a control), T2: 80% soil + 20% compost, T3: 60% soil + 40% compost, T4: 40% soil + 60% compost, T5: 20% soil + 80% compost & T6: 100% compost. Results revealed that number of fruit, fruit yield and total sugar (%)was increased with the increasing level of compost up to 80% after that decreased at 100% compost. The treatment T5: 20% soil + 80% compost gave the best results among the treatments to grow strawberry with good yield (185.3 g/plant) and sweetness (total sugar 5.19%). On the other hand, six treatments i.e. T1: Control, T2: Compost (5 t/ha), T3: Compost tea (50% concentration), T4: Compost (5 t/ha) + Compost tea (50% concentration), T5: Compost tea (100% concentration) and T6: Compost (5t/ha) + Compost tea (100% concentration) were considered in tomato experiment. As a result, it was observed that combined application of compost (5 t/ha) along with compost tea (100% conc.) (T6) gave the highest yield of tomato than not only control (T1) but also single application of compost or compost tea (T2, T3, T4&T5). Level of compost tea concentration also showed significant effect on fruit yield of tomato. Comparing between treatment T4 and T6, fruit yield was found higher (1027.67 g/plant) in treatment T6: Compost (5t/ha) + Compost tea (100% conc.) than 961.3 g/plant in T4: Compost (5 t/ha) + Compost tea (50% conc.). So, it could be summarized that use of rice straw as compost and compost tea affects positively both in two experiments. The results of this study confirm the beneficial effects of compost to increase the yield and sweetness of strawberry and combination of compost and compost tea to increase the yield of tomato. Progressive Agriculture 30 (4): 335-343, 2019